2016
DOI: 10.3389/fmicb.2016.00979
|View full text |Cite
|
Sign up to set email alerts
|

Bifidobacteria and Butyrate-Producing Colon Bacteria: Importance and Strategies for Their Stimulation in the Human Gut

Abstract: With the increasing amount of evidence linking certain disorders of the human body to a disturbed gut microbiota, there is a growing interest for compounds that positively influence its composition and activity through diet. Besides the consumption of probiotics to stimulate favorable bacterial communities in the human gastrointestinal tract, prebiotics such as inulin-type fructans (ITF) and arabinoxylan-oligosaccharides (AXOS) can be consumed to increase the number of bifidobacteria in the colon. Several func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

40
967
7
18

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 1,267 publications
(1,032 citation statements)
references
References 185 publications
(290 reference statements)
40
967
7
18
Order By: Relevance
“…In addition, inulin can stimulate the metabolic activity of Roseburia spp. and E. rectale genera of the Firmicutes phylum (117,118). Roseburia spp.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, inulin can stimulate the metabolic activity of Roseburia spp. and E. rectale genera of the Firmicutes phylum (117,118). Roseburia spp.…”
Section: Introductionmentioning
confidence: 99%
“…Cani et al [8] demonstrated that lipopolysaccharide, a component of certain gram negative bacterial membranes, can translocation across a "leaky" gut wall, stimulating a cascade of inflammatory cytokine release, increased adiposity, and hyperglycemia. Gungor et al [9] recently described fecal microbiomal shifts among individuals with SCI resulting in reduced production of butyrate, a fatty acid instrumental in preserving gut barrier functions [10]. While our data and the scope of this preliminary work are insufficient to support conclusions about metabolic effects of neurogenic bowel, they raise the possibility of a unifying explanation (microbiomal perturbations with resulting "leaky" gut) for both the adipose deposition in skeletal muscle and the post-prandial hyperglycemia often seen in people with SCI.…”
Section: Discussionmentioning
confidence: 99%
“…Известно, что Eubacterium cylindroides является важным источником бутирата -од-ного из важнейших противовоспалительных факторов, продуцируемых симбиотическими бактериями кишечника [17]. К продуцентам бу-тирата, предположительно оказывающим про-биотическое влияние, относят также бактерии родов Anaerostipes, Fusicatenibacter, Roseburia, Blautia, Coprococcus и видов Clostridium populeti, Roseburia faecis и Roseburia intestinalis, повышенные в группе пациентов с другими неврологическими заболеваниями [18][19][20]. Снижение представленности бактерий Roseburia, Blautia и Coprococcus в кишечной микробиоте при болезни Паркинсона отмечалось также при сравнении со здоровыми людьми в исследовании, проведенном на американской популяции [8].…”
Section: Discussionunclassified